Employing the policy capacity framework for health system strengthening. Issue 1 (25th January 2023) - Saddi, Fabiana da Cunha; Peckham, Stephen; Bloom, Gerald; Turnbull, Nick; Coelho, Vera Schattan; Denis, Jean-Louis
Abstract: The policy capacity framework offers relevant analytical ideas that can be mobilized for health system strengthening. However, the employment of this framework in the health field constitutes a relevant interdisciplinary gap in knowledge. This themed issue explores the relationships between the policy capacity framework and health system strengthening, in a multidimensional and interdisciplinary way, in high-income and low–middle-income countries. This introduction unpacks the dynamic interrelationships between the policy capacity framework and health system strengthening, bringing together common and distinct elements from both fields and summarizing possible relationships between them. The analysis shows that both fields together can increase our knowledge on health policies and system's critical themes and reforms. This challenge could be followed by exploring the convergences between them, as far as concepts/themes (types of capacities and other themes) and levels of analysis are concerned. Although in varied ways, papers in this issue (based on European countries, China, Canada, New Zealand, India, Australia, and Brazil) advance the use of the policy capacity framework for health policy or system strengthening. They give two main interdisciplinary contributions. Critical capacities can be incorporated into the policy capacity framework for the analysis of system strengthening—capacity to adapt, contexts of mixed and complex systems, dynamic view of policy capacity, and policy capacity as a relational power. Policy capacity is contextually interpreted (relative to the problem frame) and dynamic and adaptive (processual and relational), in relation to the properties of a health system, particularly with regard to the existing and developing mixed and complex systems.